Diagnosis of Dynamic Topology MANETs in Faulty Environment (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper we describe here the diagnosis the dynamic topology in a faulty environment. In this paper we have optimize that type of network in which less nodes are used to reach source to destination so that data loss are reduced. we have compare the dataÂ  loss after optimize the new path to reach the source to destination. In dynamic topology nodes are free to move randomly. Mobile stations from an arbitrary topology.